Impact of putting green management on visible wear damage caused by foot traffic. (7th January 2021) - Nikolai, Thomas A.; Karcher, Douglas E.; Hathaway, Aaron D.; O'Brien, Daniel
Abstract: A 2‐yr study was conducted at Michigan State University (MSU) and the University of Arkansas (UARK) to identify creeping bentgrass ( Agrostis stolonifera L.) putting green management practices that minimize or exacerbate visible wear damage (VWD) caused by aggressive golf shoes or cleats. Management treatments included different levels of grooming (none vs. three times weekly at a depth of 0.5 mm), lightweight rolling (none vs. three times weekly), sand topdressing (none vs. every 14 d at the rate of 0.6 L m −2 ), and nitrogen fertility (low N vs. high N every 14 d) applied as urea at the rates of 0.6 or 1.2 g m −2 . Rolling significantly increased VWD at UARK in both years and at MSU in 2017. When increases in VWD occurred on rolled plots, there were also significant increases in moisture in the top 3.8 cm of the root zone. Higher fertility consistently increased VWD at UARK throughout the study and after a single traffic event at MSU. Throughout the trial, grooming and sand topdressing occasionally reduced VWD at both locations. These results will help agronomists and golf course superintendents fine‐tune cultural practices to mitigate VWD on intensively managed creeping bentgrass putting greens.